Availing entitlements under Janani Shishu Suraksha Karyakram in Tamil Nadu: a reality - Chellaiyan, Vinoth Gnana; Christopher, Christina S. C.; Daral, Shailaja (International Journal Of Community Medicine And Public Health, 2018)
Background: Janani Shishu Suraksha Karyakram (JSSK) was launched in India to improve maternal and child healthcare, and to alleviate out of pocket expenditure on healthcare. The objective was to analyze the awareness and utilization of the JSSK entitlements among residents in Kancheepuram district of Tamil Nadu. Methods: This cross sectional study was conducted in Thriuporur block, which was selected randomly from 13 blocks of Kancheepuram district. Two primary health care centers - Ezhichur and Thiruporur of Thriuporur block, were selected based on population proportion to size. A total of 80 mothers who had recently delivered a live child were selected randomly from these two PHCS. The data was collected through house to house visits by trained interviewers using a pretested, validated, structured questionnaire. Results: Mean age of the participants was 24.58 (±3.32) years. Around fifty two participants were aware about the scheme. Better awareness was seen with higher literacy and higher socioeconomic status (p=-0.043, 0,032). Cashless deliveries (100%) and free drugs (100%) were availed by all participants and among the neonates, free diagnostics (100%) and blood transfusions (100%) were availed by all. Transportation services to and from health institutions were utilized by 1.2% of the participants. Majority of the participants (98%) spent on conveyance to and from hospital. Conclusions: Though the study revealed good awareness of the scheme among the participants, it showed insight into the existing gaps in utilization of these services. Further effort is required in providing additional information on JSSK and its services within institutions and at the community level.